Aging and antioxidants: the impact of dietary carotenoid intakes on soluble klotho levels in aged adults - He, Xingkang; Yin, Xin; Chen, Xin; Chen, Xiaoli (Frontiers in Endocrinology, 2023)
The association between dietary carotenoid intake and Soluble Klotho (S-Klotho) levels among the elderly population requires further evaluation. The purpose of this study is to evaluate the relationship between the dietary carotenoid intake and the S-Klotho plasma levels in older adults.Methods: Eligible participants aged 60 years or above were selected from the National Health and Nutrition Examination Surveys (NHANES) data, collected between 2007 and 2016. The consumption of carotenoids was determined through two 24-hour dietary recall assessments.Moreover, the S-Klotho levels in the serum were measured using an Enzyme-Linked Immuno-Sorbent Assay (ELISA).Results: A total of 5,056 participants were included in the study having a median total carotenoid intake of 9775.25 μg (95% confidence interval (CI): 8971.30−10579.21) and a median S-Klotho concentration of 815.59 pg/mL (95% CI: 802.59−828.60). The multivariable regression analysis showed that a single standard deviation increase in total carotenoid intake was significantly associated with an 8.40 pg/mL increase in S-Klotho levels (95% CI: 0.48−16.31). When the carotenoids were divided into quartiles, participants in the third ((4963.5μg/day,11662.5μg/day]) and fourth quartiles ((11662.5μg/day,377178μg/day]) showed higher S-Klotho levels compared to those in the first quartile. Among carotenoid subtypes, increased intake of α-carotene, β-carotene, and lutein with zeaxanthin was associated with elevated S-Klotho levels. These observed associations between carotenoid subtypes and S-Klotho levels remained consistent across male participants, having a normal weight, and a moderate physical activity based on stratified analysis.The total carotenoid intake was positively related to plasma levels of S-Klotho in the elderly population, particularly for α-carotene, β-carotene, and lutein with zeaxanthin. However, further research is needed to confirm these findings and explore the underlying mechanisms behind this relationship.